A Miniaturized Optical Sensor with Integrated Gas Cell. (2015) - Ayerden, N.P.; Ghaderi, M.; de Graaf, G.; Wolffenbuttel, R.F.
Abstract: The design, fabrication and characterization of a highly integrated optical gas sensor is presented. The gas cell takes up most of the space in a microspectrometer and is the only component that has so far not been miniaturized. Using the tapered resonator cavity of a linear variable optical filter as a gas cell enables ultimate miniaturization, while maintaining robustness without any moving parts. Multiple reflections from highly reflective mirrors allow a 24-25.5 μm long resonator cavity to also act as a gas cell with an equivalent optical absorption path length of 6 mm.